Crystallinity enhancement of extruded polypropylene containing poly(vinyl alcohol) fibers prepared in situ. (21st July 2022) - Nishikawa, Riho; Eno, Ayaka; Janchai, Khunanya; Han, Ruiqi; Kida, Takumitsu; Mori, Toyoichiro; Aridome, Norifumi; Miyamoto, Akira; Yamaguchi, Masayuki
Abstract: The present paper describes a novel method for reinforcing isotactic polypropylene (PP) by adding poly(vinyl alcohol) (PVA) fibers prepared by melt-stretching. Low-viscosity PVA droplets were deformed into fibers in the molten PP by melt-stretching them beyond the melting point of PVA. When the obtained composite was extruded below the melting point of PVA, the fibers became oriented toward the flow direction. The PVA demonstrated marked nucleating activity with regard to PP crystallization, which was further promoted by enlargement of the surface area by fibrillization. As a result, there was virtually no orientation relaxation of the PP chains with an increase in crystallinity, which explains the improvement in rigidity of the reinforced composite. Graphical abstract: Image 1 Highlights: PVA fibers were well dispersed in PP by melt-mixing. PVA fibers act as a nucleating agent for PP. Chain orientation and crystallinity of PP were enhanced by the PVA addition. Modulus of the extruded sample was enhanced by PVA fibers.